Debt theories in Islamic commercial transactions and their implications for the Islamic capital market - Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa (New Millennium Discoveries, UK, 2019)
There are two different approaches to the prophetic concern regarding debt acquisition and the related rulings. The Prophet (peace be upon him) was recorded as having discouraged debt while other verbal traditions provided guidelines on how to manage debt in a socially responsible manner. This paper aims to analyse these two contrary views according to the Maqasid Shariah and look at how this has impacted juristic rulings. Furthermore, the paper reviews classical fiqh theories on debt, sale of debt, alMuqassah, Suftajah, Hawalah, and Ibra. The paper also reviews the theoretical perspective on the sale of debt according to the understanding of Islamic scholars across the schools of Islamic Jurisprudence which has a substantial impact on the contemporary practices in Islamic banking and the Islamic capital market.